Endemic Hemicryptophyte Grasslands of the High Mountains of the Caribbean - Cano-Ortiz, Ana (2022)
Although there are numerous studies on the floristic composition of the Andean and Car-ibbean grasslands, there are limited information from a phytosociological point of view. This work therefore aims to highlight the differences in this important vegetation type in these two biodiver-sity hotspots to gain a better understanding of their floristic and vegetational richness. The floristic composition of Andean grasslands (Ecuador) and the island of Hispaniola is also studied. The rea-son for this comparative analysis of Andean and Caribbean territories is their tropical character and their bioclimatic similarities. The comparative analysis of Peruvian Andean and Colombian grass-lands is based on floristic knowledge from the literature, our inventories on the island of Hispaniola, and the works of Peguero. We applied the phytosociological methodology of Braun-Blanquet and the code of phytosociological nomenclature. We performed a statistical analysis to verify the differ-ences between both community types using the statistical packages PAST© and CAP3. The com-parative analysis of Andean and Caribbean grasslands shows a clear floristic and biogeographical differentiation and reveals that the only ecological character they share is their high-mountain at-tribute. In the Caribbean these communities are found only on the island of Hispaniola (Dominican Republic) in the Central biogeographic sector, Central subprovince, Hispaniola province. These grasslands are exclusive to Hispaniola and have a high rate of endemics. We propose the following new syntaxa: the association Hyperico constanzae-Danthonietum domingensis, the alliance Hieracio domingensis-Deschampsion domingensis, the order Danthonietalia domingensis, and the class Des-champsio-Danthonietea domingensis. We found high biodiversity values for Andean and Caribbean areas. This is due to the intense anthropic activity on the island of Hispaniola, which has led to a high percentage of naturalized plants.